The Influence of Microwave on Reduced Graphene Oxide (rGO) Crystallinity from Inorganic Waste - Lubis, Lailatul Husna; Husnah, Miftahul (Phi: Jurnal Pendidikan Fisika dan Terapan, 2020)
The synthesis of reduced graphene oxide was carried out using the smoke catcher method and inorganic waste. The inorganic waste smoke obtained became the basic material as a carbon source. After burning the inorganic waste, the smoke collected was in the form of a powder and exposed to microwaves. Based on FTIR characterization, the synthesis was successfully carried out by obtaining ~ 1600 cm-1 as the peak of the aromatic functional group (C = C) or graphene functional group. After the inorganic waste smoke sample was put in the microwave, the rGO sample was obtained which had a higher crystallinity than before heating in the microwave.